112k views
5 votes
Write your answer in order of decreasing powers of x.

(18x 5 + 6x 4 - 12x 3) ÷ 6x 2

2 Answers

5 votes
The answer is: " 3x³ + x² − 2x " .
________________________________________________________
Step-by-step explanation:
_________________________________________________________

Take the first expression; or the "numerator" ;

and "factor out" a: " 6x² " :
___________________________________________________________


(18x^5+6x^4-12x^3)/(6 x^(2) ) = (6x^2(3x^3+x^2-2x))/(6x^2) ;

→ Both " 6x² " values "cancel out to 1" ;

→ since: " { 6x² / 6x² = 1 } " ;

And we have: " 3x³ + x² − 2x " .
________________________________________________________
User Lauran
by
5.1k points
3 votes

(18x^5 +6x^4 - 12x^3)/(6x^2) = ((6x^2)(3x^3 +x^2 - 2x))/(6x^2) = 3x^3 +x^2 - 2x
User Manishoaham
by
5.7k points